SYNTHESIS, CHARACTERIZATION AND EVALUATION OF ANTICANCER ACTIVITY OF SOME NEW SCHIFF BASES OF 1, 3, 4-THIADIAZOLE DERIVATIVES - Naskar, Arup; Singha, Tanushree; Guria, Tanmoy; Singh, Jagadish; B, Ashok Kumar; Maity, Tapan Kumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: N-benzylidene-5-phenyl-1, 3, 4-thiadiazol-2-amine derivatives: Synthesis and anticancer activity. Methods: In the present study five new derivatives of N-benzylidene-5-phenyl-1, 3, 4-thiadiazol-2-amine (Schiff bases containing 1, 3, 4-thiadiazole) were synthesized according to the literature methods and were characterized by FT-IR, 1H NMR spectroscopy and C, H, N analysis. Anticancer activity was evaluated in Male Swiss albino mice using Ehrlich's Ascites carcinoma cells. Compounds were administered at a dose of 25 mg/kg, body weight intraperitoneally. Results: The compounds were found to reduce tumor volume, viable cell count and increase the tumor weight (%) inhibition, ascites cells (%) inhibition, non-viable cell count and increase in life span (%ILS). All the compounds exhibited significant (P< 0.01) anticancer activity compared to control and the compound 2d & 4d was found to be most potent. Conclusion: It is concluded that synthesized Schiff bases of 2-amino-5-aryl-1, 3, 4-thiadiazoles derivatives are biologically active and developed into useful anticancer agents. Â